HUBUNGAN LAMANYA PENGGUNAAN KB SUNTIK 3 BULAN TERHADAP PERUBAHAN SIKLUS MENSTRUASI DI BPS NY. S DESA SAMBIREJO, SEMARANG - Novia Mahdalena; Tut Wuri Prihatin; Hermeksi Rahayu (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Background : Family planning is deed that helps individuals or married couples to avoid unwanted births, get the birth that is wanted, set the interval between pregnancies, birth control when the current time in intercourse to the age of husband and wife, and to see the number of kids in the household. One of contraception that most people demand is 3months KB injecting as much as 52.05 %. The purpose of this research is to know how long use of 3 months injection contraceptive against of menstruation cycle in BPS NY. S Desa Sambirejo, Kecamatan Gayamsari, Semarang.    Method : The type of this research is using the correlation study of the cross-sectional approach. The total sample of this research was 51 respondents using the purposive random sampling technique. This research taken in BPS Ny. S Desa Sambirejo, Semarang. Test data analysis was using a Chi Square test. Result : The result of this research showed the average age from 51 acceptors of 3 months KB Injection in BPS NY. Sri Wahyuni was 30 years old and mostly they had been in the middle educated around 31 respondents (60,8 %) with the length of duration more than 5 years was 27 respondents (52,9 %). The data showed that there were 30 respondents ( 58.8 % ) who experience irregular periods. Statistical test results obtained p - value = 0.039 < 0.05Conclution : hypothesis ( Ho )  rejected and Hypothesis ( Ha ) accepted means there is significant relationship between the  duration of 3 -month injectable contraceptive against of the changing cycle of menstruation in BPS Ny . S Sambirejo Gayamsari, Semarang.